The EU and China in African Authoritarian Regimes Domestic Politics and Governance Reforms - Hackenesch, Christine (Governance and Limited Statehood, 2018)
Political science; EU; China; Africa; Rwanda; Ethiopia; Angola; Survival strategy; Governance; Reform; Economic dependence; Paul Kagame; 2005 Ethiopian general election; African oil revenues; Authoritarian regimes; Party regimes